ASUHAN KEBIDANAN PADA NEONATUS NY. “S” DI RUMAH BERSALIN BUNDA PUJA TEMBILAHAN TAHUN 2019 - Ariska, Wika; Astuti, Haryati; Madinah, Madinah (Jurnal Kesehatan Husada Gemilang, 2022)
Neonatal are the first period of life outside the womb until the age of 28 days. The infant mortality rate (Kemenkes, 2018) in Indonesia is 185/day, AKN 15 per 1000 live births. Based on the Dinkes Profile (2019), the number of neonatal deaths in Indragiri Hilir Regency is 21 neonatal deaths and a complete KN of 79.9% means that it has not reached the SPM target. This obstetric care is to provide care for Mrs. "S" neonates at the Mother's Maternity Home Puja Tembilahan in 2019 using Varney's thinking flow method and documented in the form of SOAP. From the results of visits made on July 16, 2019 to August 03, 2019 as many as 3 times, KN1 (11 hours) was carried out at RB, KN2 (5 days) and KN3 (20 days) were carried out at home. From the results of the implementation of the upbringing, there are theoretical and practical gaps, namely the non-examination of SHK and the discrepancy in the timing of the provision of HB0 immunization on KN1 and no BB weighing on KN2 and KN3. It is hoped that the caregiver will be able to pay attention to and carry out every type of service to neonates and the Bunda Puja Maternity Home is expected to improve the quality of services for neonates by facilitating SHK examination equipment or collaborating with more adequate facilities. Neonatus adalah masa kehidupan pertama diluar rahim sampai dengan usia 28 hari. Angka kematian bayi (Kemenkes, 2018) di Indonesia 185/hari, AKN 15 per 1000 kelahiran hidup. Berdasarkan Profil Dinkes (2019) jumlah kematian neonatus di Kabupaten Indragiri Hilir sebanyak 21 kematian neonatus dan KN lengkap 79,9% artinya belum mencapai target SPM. Asuhan kebidanan ini untuk memberikan asuhan pada neonatus Ny. “S” di Rumah Bersalin Bunda Puja Tembilahan tahun 2019 dengan menggunakan metode alur fikir Varney dan didokumentasikan dalam bentuk SOAP. Dari hasil kunjungan yang dilakukan pada 16 Juli 2019 sampai dengan 03 Agustus 2019 sebanyak 3 kali, KN1 (11 jam) dilakukan di RB, KN2 (5 hari) dan KN3 (20 hari) dilakukan dirumah. Dari hasil pelaksanaan asuhan terdapat kesenjangan teori dan praktik yaitu tidak dilakukannya pemeriksaan SHK dan ketidaksesuaian waktu pemberian imunisasi HB0 pada KN1 dan tidak dilakukan penimbangan BB pada KN2 dan KN3. Diharapkan pemberi asuhan untuk dapat memperhatikan dan melaksanakan setiap jenis pelayanan pada neonatus dan Rumah Bersalin Bunda Puja diharapkan dapat meningkatkan mutu pelayanan pada neonatus dengan memfasilitasi peralatan pemeriksaan SHK atau melakukan kerja sama ke fasilitas yang lebih memadai.